Water in Circular Economy and Resilience : The Case of Sao Paulo, Brazil - World Bank (World Bank, Washington, DC, 2021)
This case study is part of a series prepared by the World Bank’s Water Global Practice to highlight existing experiences in the water sector. The purpose of the series is to showcase one or more of the elements that can contribute toward a Water in Circular Economy and Resilience (WICER) system. This case focuses on the experience of Sao Paulo, Brazil.